Impending spontaneous tracheal rupture due to steroid use. (May 2022) - Koh, Yi Zhe; Sewa, Duu Wen; Soo, Ing Xiang
A spontaneous tracheal rupture is rare and life-threatening. We postulate that long-term steroid administration is an under-reported risk factor. We present a case of an impending spontaneous tracheal rupture in a 51-year-old female with a significant medical history of systemic lupus erythematosus and interstitial lung disease, and a drug history of chronic steroid intake for 9 months. An impending tracheal rupture was diagnosed by computed tomography, which prompted surgery. A right thoracotomy, followed by a posterior tracheal repair via an intercostal muscle flap, was done, with venovenous extracorporeal membrane oxygenation support throughout the operation.